Leeuwin Current Dynamics over the Last 60 Kyr - Relation to Australian Ecosystem and Southern Ocean Change - Karas, C (Copernicus Publications, 2022)
The Leeuwin Current, flowing southward along the western coast of Australia, is an important conduit for the poleward heat transport and inter-ocean water exchange between the tropical and the subantarctic ocean areas. Its past development and its relationship to Southern Ocean change and Australian ecosystem response is, however, largely unknown. Here we reconstruct sea surface and thermocline temperatures and salinities from foraminiferal-based Mg/Ca and stable oxygen isotopes from areas offshore of southwestern and southeastern Australia, reflecting the Leeuwin Current dynamics over the last 60 kyr. Their variability resembles the biomass burning development in Australasia from ∼60-20 ka BP, implying that climate-modulated changes related to the Leeuwin Current most likely affected Australian vegetational and fire regimes. Particularly during ∼60-43 ka BP, the warmest thermocline temperatures point to a strongly developed Leeuwin Current during Antarctic cool periods when the Antarctic Circumpolar Current (ACC) weakened. The pronounced centennial-scale variations in Leeuwin Current strength appear to be in line with the migrations of the Southern Hemisphere frontal system and are captured by prominent changes in the Australian megafauna biomass. We argue that the concerted action of a rapidly changing Leeuwin Current, the ecosystem response in Australia, and human interference since ∼50 BP enhanced the ecological stress on the Australian megafauna until its extinction at ∼43 ka BP. While being weakest during the Last Glacial Maximum (LGM), the deglacial Leeuwin Current intensified at times of poleward migrations of the Subtropical Front (STF). During the Holocene, the thermocline off southern Australia was considerably shallower compared to the short-term glacial and deglacial periods of Leeuwin Current intensification. Copyright © 2022 Dirk Nürnberg et al.